La Cirugía General y la conducta a seguir ante pacientes sospechosos de COVID-19 - Díaz-Rodríguez, Yusnier Lázaro; Vargas-Fernández, María de Los Ángeles (EsTuSalud, 2020)
La Cirugía General y la conducta a seguir ante pacientes sospechosos deCOVID-19